2016
DOI: 10.1111/ejn.13479
|View full text |Cite
|
Sign up to set email alerts
|

Steady‐state VEP responses to uncomfortable stimuli

Abstract: Periodic stimuli, such as op-art, can evoke a range of aversive sensations included in the term visual discomfort. Illusory motion effects are elicited by fixational eye movements, but the cortex might also contribute to effects of discomfort. To investigate this possibility, steady-state visually-evoked responses (SSVEPs) to contrast-matched op-art-based stimuli were measured at the same time as discomfort judgements. On average, discomfort reduced with increasing spatial frequency of the pattern. By contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Prior studies that have measured ssVEP in response to flickering stimuli have found a weak ( O'Hare, 2017 ) or negative ( Bjørk, Hagen, Stovner, & Sand, 2011 ) correlation between visual discomfort and visual cortical response. Bjørk et al (2011) reported a negative correlation of visual discomfort and the cortical response evoked by flickering stimuli, finding larger cortical responses for slower temporal frequencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies that have measured ssVEP in response to flickering stimuli have found a weak ( O'Hare, 2017 ) or negative ( Bjørk, Hagen, Stovner, & Sand, 2011 ) correlation between visual discomfort and visual cortical response. Bjørk et al (2011) reported a negative correlation of visual discomfort and the cortical response evoked by flickering stimuli, finding larger cortical responses for slower temporal frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond this general proposal, however, the link between specific stimulus properties, visual discomfort, and cortical response is less clear. Only a weak or even absent correlation between visual discomfort and evoked cortical response in people without migraine has been found for stimuli varying in spatial frequency (Huang, Cooper, Satana, Kaufman, & Cao, 2003;O'Hare, 2017). Studies of sensitivity to patterns and temporal flicker have generally been made using blackand-white patterns, which probe only a small set of possible stimulus properties that may be associated with visual discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies that have made use of ssVEP have found a weak (O'Hare, 2017) or negative (Bjørk, Hagen, Stovner, & Sand, 2011) correlation between visual discomfort and visual cortical response. We believe that an important difference between this prior work and our study is the isolation of the induced periodic signal component from the aperiodic component (Haller et al, 2018).…”
Section: Comparison With Prior Studiesmentioning
confidence: 90%
“…Moreover, visual discomfort can occur when reading texts, for example, letters moving, flickering, or disappearing, and consequently can hinder reading comprehension [ 4 , 5 ]. The origin of visual discomfort is partly in the sensory and neuronal responses to the physical properties of visual stimuli; for example, their spatial frequency [ 3 , 6 8 ] and Fourier energy distribution [ 9 12 ]. Another origin can be attributed to individual clinical conditions such as photosensitive epilepsy [ 3 , 6 , 13 , 14 ] and migraine headache [ 3 , 15 21 ], whose perceptual and neuronal hyperactivities have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have examined visual discomfort and its variation in normal and clinical populations based on behavior (e.g., [ 9 ]), electrophysiology (e.g., [ 8 ]), and brain imaging [ 18 , 25 27 ]. On the contrary, psychometric scales can also be useful when investigating perceptual inter-individual variability.…”
Section: Introductionmentioning
confidence: 99%